Computing Orbits of Big Fullerenes - YAVARI, MORTEZA; REZA ASHRAFI, ALI (Asian Journal of Chemistry, 2010)
An Euclidean graph associated with a molecule is defined by a weighted graph with adjacency matrix M = dij, where for i≠j, dij is the elucidean distance between the nuclei i and j. In this matrix dij can be taken as zero if all the nuclei are equivalent. Otherwise, one may introduce different weights for distinct nuclei. In this paper the symmetry of the big fullerene C320 with point group symmetry Ih together with its orbits is computed.